Enrichment as a conservation tool to enhance behavior, morphology, gene expression, and survival in Arkansas darters - Kopack, Christopher J., author; Angeloni, Lisa, advisor; Fetherman, Eric, advisor; Ghalambor, Cameron, committee member; Kanno, Yoichiro, committee member (Colorado State University. Libraries, 2023)
Conservation practitioners often rely on captive breeding programs to supplement wild populations at risk of extinction. While population augmentation has been successful for some taxa, the use of hatchery fish to supplement wild populations can be severely impacted by predation. Elevated predation on hatchery fish may arise because hatchery environments often differ starkly from wild environments, constraining the ability of hatchery fish to phenotypically match the environments in which they are targeted for release. Phenotypic mismatch caused by differences between hatchery and wild environments can limit efforts to conserve fish species at risk of extinction when hatchery-reared fish are used to augment wild populations. Phenotypes adapted to or induced by hatchery environments are thought to be maladapted for life in the wild. Thus, enriching the hatchery environment (abiotically and biotically) to make it more similar to the wild may induce phenotypes, including behavior, morphology, and gene expression profiles, that are better suited to the environments fish will experience after release. Chapter One explores how hatchery-reared fish respond to novel predators and whether those responses can be enhanced to improve survival. Identifying the presence of innate predator recognition and the capacity for learning to recognize predators can inform conservation management practices. We assessed antipredator behavior (time spent moving and distance from a predator) and the efficacy of predator training for three populations of a species of conservation concern, the Arkansas darter (Etheostoma cragini), which is vulnerable to predation by esocid predators like the introduced northern pike (Esox lucius). Arkansas darters demonstrated an innate ability to recognize and respond to a novel esocid predator. Their behavior also changed in response to predator cues (training), though the direction of response to cues was opposite our prediction. Populations differed in their response to the predator treatment, highlighting the potential value of managing populations separately. Our results suggest that antipredator behavior is innate and that exposure to predator cues does affect behavior. This study demonstrates the importance of evaluating enrichment practices and incorporating behavioral observations into conservation programs to guide population-specific management decisions. In Chapter Two, we used a factorial approach to assess whether abiotic enrichment and biotic enrichment (predator recognition training) increase survival of Arkansas darters during encounters with a novel predator. We also assessed the effects of abiotic enrichment on the expression of behavioral and morphological phenotypes across three populations. Morphology and behavior differed among populations and between abiotic treatments, and populations responded differently to the abiotic treatments. Furthermore, we found that in combination with predator training, abiotic enrichment increased the probability of surviving a first encounter with a predator. We therefore recommend conservation practitioners incorporate abiotic enrichment and predator recognition training in the hatchery, as any increase in survival is expected to benefit efforts to conserve this species. In Chapter Three, we took a molecular approach (TagSeq) to elucidate how abiotic enrichment and biotic enrichment impacts the whole-brain gene expression of Arkansas darters, comparing the effects in two hatchery populations to a wild reference population. Although, we found no effect of biotic enrichment on gene expression, we did find that abiotic enrichment has the potential to reduce phenotypic mismatch between hatchery and wild fish, indicating that enrichment may aid current conservation efforts. Overall, these studies suggest a potential role for enrichment in the conservation of imperiled fish, and they highlight the value of a phenotypic approach to managing populations.
Keywords: Esox lucius; evolution; plasticity; Etheostoma cragini; antipredator behavior; hatchery